Bending the cost curve in the United States: the role of comparative effectiveness research - Ghaferi, Amir A (BioMed Central, 2010)
Owing to an increasing focus on the rising cost of medical care in the United States, bending the cost curve has become the central tenet of healthcare reform. The exact definition of this phrase, however, remains elusive. In order to affect change in the cost and quality of healthcare, the importance of comparative effectiveness research must be recognized.